1968
DOI: 10.1084/jem.128.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Germinal Centers in Lymphoid Tissue to Immunological Memory

Abstract: Transfer of adoptive immunity has proved useful in detection and characterization of the ceils carrying immunological memory. By introducing varying time intervals between transfer and reexposure to antigen in the recipients, the duration of responsiveness of memory cells was defined. Perkins and Makinodan (1) showed that, with donor ceils taken 4--6 wk after sensitization, little change in responsiveness of the primed cells occurs over the first few days following transfer. The results of Dresser (2) and Cela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1969
1969
1984
1984

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In terms of formation of sensitized cells, the marked depression of the 7S memory after passive immunization at 24 hr (in contrast to the enhancement of 19S memory) corresponds to the suppressed growth of germinal centers during the primary response. Thus, if the germinal center is, as has been suggested, a site of the proliferative expansion of immunocompetent cells (17,12), these data indicate that the germinal center growth is related to the 7S cellular response. The functional significance of persisting antigen in these centers appears to be more closely related to the 7S antibody response and the development of 7S memory.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In terms of formation of sensitized cells, the marked depression of the 7S memory after passive immunization at 24 hr (in contrast to the enhancement of 19S memory) corresponds to the suppressed growth of germinal centers during the primary response. Thus, if the germinal center is, as has been suggested, a site of the proliferative expansion of immunocompetent cells (17,12), these data indicate that the germinal center growth is related to the 7S cellular response. The functional significance of persisting antigen in these centers appears to be more closely related to the 7S antibody response and the development of 7S memory.…”
Section: Discussionsupporting
confidence: 61%
“…Although the functional significance of this antigen deposition is not completely resolved, experimental evidence demonstrates that there may be a causal relationship between the antigen localization and the presence and proliferation of the characteristic, large pyroninophilic cells of the germinal centers (8,12). These cells by morphologic and functional parameters are considered immunologically competent cells (13)(14)(15)(16)(17).We have further suggested that during the primary immune reaction the persistence of antigen in germinal centers is a dynamic process which is sensitive to and altered by the level of free specific antibody (18). Studies of Sahiar and Schwartz (19) showed that rabbits receiving heterologous passive antibody 1 hr after antigen had a marked decrease in germinal center hyperplasia during the primary response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has also been presented that germinal centers are linked in some way to the enhanced antibody synthesis associated with immunological memory (27,76,77). Immunological memory, as usually defined, is known to be associated with synthesis of IgG molecules (27).…”
Section: Discussionmentioning
confidence: 99%
“…These dendritic processes in turn are in intimate contact with lymphocytes and blastoid ceils (52). The lymphocytes in germinal centers, many of which are actively replicaring cells, have been regarded as precursors of plasma cells (21,(34)(35)(36)(37)80), or possible "memory cells" (12,73,76,77).Other authors have described the presence and production of immunoglobulins and antibodies in germinal centers (8,15,16,45,49,59,80,81). However, Pernis has submitted evidence that at least some of the immunoglobullns present in germinal centers are not synthesized locally (61).Germinal centers have been associated with antibody and immunoglobulin production in other ways.…”
mentioning
confidence: 99%